Ecotourism; Implementation of Security Management Concepts - Untari, Dhian Tyas (Journal of Economic Development, Environment and People, 2020)
The following paper is an essay book review, examines and links the concept of ecotourism and the concept of security management. It is hoped that this essay will become a new topic for academics and practitioners.